2018
DOI: 10.1039/c8nr01588k
|View full text |Cite
|
Sign up to set email alerts
|

Selectively arranged single-wire based nanosensor array systems for gas monitoring

Abstract: Gas nanosensors, comprised of arrays of nanoelectrodes with finger-widths of ∼100 nm developed by electron beam lithography and aerosol assisted chemical vapor deposited non-functionalized and Pt-functionalized tungsten oxide nanowires (<100 nm) subsequently integrated across the pairs of electrodes via the dielectrophoresis method, are developed in this work. The functionality of these devices is validated towards various concentrations of NO2 and C2H5OH. The results demonstrate reproducible and consistent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Results obtained with platinum-doped WO 3 appear possibly contradictory. Chmela et al reported that platinum addition to WO 3 nanowires (<100 nm) caused detrimental effects, with lower sensitivity and selectivity toward NO 2 compared with the unfunction-alized systems, associated with better sensing properties toward C 2 H 5 OH [325]. On the opposite, with nitrided WO 3 (WO x N y nanofibers), platinum addition enhanced the gas sensing characteristics by (i) lowering the operating temperature; (ii) enhancing the sensor reversibility at 50 • C; and (iii) exhibiting an exceptional selectivity toward NO 2 against interfering molecules such as C 2 H 5 OH, C 7 H 8 , CH 4 , CO, NH 3 and NO [326].…”
Section: Wo 3 -Based Sensor For No 2 Detectionmentioning
confidence: 99%
“…Results obtained with platinum-doped WO 3 appear possibly contradictory. Chmela et al reported that platinum addition to WO 3 nanowires (<100 nm) caused detrimental effects, with lower sensitivity and selectivity toward NO 2 compared with the unfunction-alized systems, associated with better sensing properties toward C 2 H 5 OH [325]. On the opposite, with nitrided WO 3 (WO x N y nanofibers), platinum addition enhanced the gas sensing characteristics by (i) lowering the operating temperature; (ii) enhancing the sensor reversibility at 50 • C; and (iii) exhibiting an exceptional selectivity toward NO 2 against interfering molecules such as C 2 H 5 OH, C 7 H 8 , CH 4 , CO, NH 3 and NO [326].…”
Section: Wo 3 -Based Sensor For No 2 Detectionmentioning
confidence: 99%
“…HRTEM analysis of the tungsten oxide NW employed in this work (Figure 2) revealed that the NWs are highly crystalline with a marked planar spacing of 3.6 Å along the NW, consistent with the unit cell of the monoclinic phase WO3 (ICCD card no. 72-0677) identified in our previous works [2,3]. The typical W4f core level XPS spectrum recorded on the tungsten oxide NWs is also shown in Figure 2 (inset).…”
Section: Resultsmentioning
confidence: 53%
“…Gas sensors based on M-NW and A-S-NW were fabricated following the same procedure described before. [2,3] Each system was mounted on a TO-8 package and contains a heating element isolated from the electrodes (either IDEs for the M-NW sensors or faced nanoelectrodes for the A-SNW sensors), see Figure 1. The integration of the gas sensitive NWs onto the IDEs was performed directly in vapor-phase via AACVD, whereas the integration of the single NWs previously grown via AACVD was performed using dielectrophoresis technique (i.e., applying an electrical potential between the nanoelectrodes during the re-deposition of NWs via drop coating).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations